Implementasi Kebijakan Desa Bengkel Kecamatan Labuapi Kabupaten Lombok Barat Dalam Pengelolaan Sampah Sistem Zero Waste - Hartiani , Dina; Zitri, Ilham (Indonesian Journal Publisher, 2024)
Waste problems have become a serious problem, especially in big cities and densely populated areas. Especially in the Bengkel Village area, Labuapi District, and West Lombok Regency, there are still piles of garbage on the side of the road and on empty land that is not a TPS. This research was conducted in Bengkel Village, Labuapi District, West Lombok Regency. This study aims to know the implementation of the zero waste management policy. This research uses qualitative methods. The data sources in this study are primary data and secondary data. The data analysis technique in this research is NVivo, the data reduction stage, data presentation and conclusion drawing. The results showed that the Implementation of the Zero Waste System Waste Management Policy has generally been implemented and realized. It can be seen from (1) The behaviour of inter-organizational relations in Bengkel Village has gone well with the commitment of the village government community leaders in realizing the Village Regulation on Waste Management and the coordination of the Village Government with the hamlet heads. (2) Lower Level Implementor Behavior has been implemented. It can be seen from the organizational control, work ethic, and professionalism of lower-level bureaucrats. (3) Target Group Behavior, namely the community, gives a positive response and supports the waste management policy in Bengkel village. Supporting factors in the Implementation of the Zero Waste System Waste Management Policy are the fleet of garbage trucks, 3-wheeled garbage transportation facilities, garbage can facilities, and sufficient waste workers. While the inhibiting factors in the Implementation of the Zero Waste System Waste Management Policy are lack of public awareness, weather constraints, lack of waste transportation facilities or meters, zero waste socialization has not been comprehensive, and the construction of TPS is constrained by location or land.